PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBANTUKAN LKS INKUIRI TERINTEGRASI GENERIK SAINS (ITGS) TERHADAP HASIL BELAJAR KETERAMPILAN DITINJAU DARI KEMAMPUAN AWAL FISIKA SISWA - Muhammad Nasir (UM Purworejo, 2016)
The aim of this study was to evaluate difference of influence between guided inquiry learning model that assisted by inquiry integrated science generic (IIBSG) student’s work sheet and guided inquiry learning model that assisted by experiment verification (EV) student’s work sheet on students’s fhysics skill learning outcomes that viewed by student’s physics prerequisite. Design of this research was tru-experimental design. Hypothesis analyzed with anacova. The result of this study is there was difference of influence between between guided inquiry learning model that assisted by inquiry integrated science generic (IIBSG) student’s work sheet and guided inquiry learning model that assisted by experiment verification (EV) student’s work sheet on students’s fhysics skill learning outcomes that viewed by student’s physics prerequisite.